Revision as of 11:44, 12 December 2008 by Mcwalker (Talk | contribs)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
$ y[n] - y[n-1] = x[n]| $
$ \Rightarrow H(\omega) = \frac {1}{1 - e^{-j \omega}} $

From table in book:

$ \begin{align} u[n] &\overset {\mathfrak{F}}{\longleftrightarrow} \frac {1}{1 - e^{-j \omega}} + \sum_{k=-\infty}^{\infty} \pi \delta (\omega - 2 \pi k) \\ 1 &\overset {\mathfrak{F}}{\longleftrightarrow} 2 \pi \sum_{l=-\infty}^{\infty} \delta (\omega - 2 \pi l) \end{align} $

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett